Genetic and environmental influences on cortisol reactivity to a psychosocial stressor in adolescents and young adults. (May 2021) - Sawyers, Chelsea; Sheerin, Christina; Eastman, Meridith; Burchett, Jason; Howell, Paul; Neigh, Gretchen; Amstadter, Ananda B.; Hettema, John; Roberson-Nay, Roxann
Abstract: Individuals vary in their response to psychological and physiological stressors, and this reactivity can be captured using measures of cortisol. Previous research suggests cortisol reactivity is under some degree of genetic control; however, the measures used have varied widely. This study (N = 524) examined potential differences in heritability across varying cortisol metrics of stress reactivity following the Trier Social Stress Test (TSST) and whether these measures are genetically or environmentally interrelated. Participants included twins aged 15–20 years (56% female). Cortisol reactivity to the TSST was assessed via serial salivary cortisol samples collected pre- and post-TSST. Modest to moderate heritability estimates (12% [95CI: 1–36%] - 45% [95CI: 16–69%]) were observed across measures purported to capture stress reactivity (peak, area under the curve [AUC], baseline-to-peak change). Findings also demonstrate both shared and unique genetic and environmental influences between baseline cortisol and cortisol reactivity. Minimal to no additional genetic innovations above and beyond the contributions of peak cortisol were found for other measures of cortisol reactivity such as AUC. This study is one of the largest twin-based samples to examine the heritability of cortisol reactivity, and results suggest that simpler measures of cortisol reactivity demonstrate higher heritability compared to more complex measurements. Highlights: Modest to moderate heritability estimates (12–45%) were observed across measures purported to capture stress reactivity. Minimal genetic innovations beyond contributions of peak cortisol were found for measures of cortisol reactivity such as AUC. Simpler measures of cortisol reactivity demonstrate higher heritability compared to more complex measurements.